Annotated Guidelines for the Simulation of Floating Offshore Wind Turbines in a Real Environmenttion on deterministic prediction of ocean surface wave and wave excitation force - Papi, Francesco; Bianchini, Alessandro (Volume 1: Offshore Technology, 2023)
In the case of floating wind turbines (FOWTs), international design standards currently leave a larger degree of freedom to engineers in the specification of the boundary conditions for turbine simulation and certification. This is due to fact that FOWTs are still a young technology, and standards are still evolving. To analyze offshore wind turbines and estimate parameters such as AEP, fatigue and extreme loads, site-specific reference environmental conditions need to be defined. Then, a probabilistic model of the installation site must be built in order to compute lifetime quantities. Finding a trade-off between simulation number and length and good long-term estimation of fatigue and ultimate loads, as well as the selection of relevant loading metrics requires a significant amount of research or experience in the field. The current work aims at exploiting a procedure that was developed within the H2020 FLOATECH project and made available open source with this study to the scientific community, with the objective of addressing what is required to perform a load and performance evaluation of a FOWT in a real environment. A procedure to obtain environmental conditions if the ones available in the literature do not meet the designer’s needs is first illustrated. Then, the most important parameters that need to be considered when performing an analysis of a FOWT are detailed; taking these into account and their corresponding metrics, a detailed guideline on how to define a suitable list of Design Load Cases (DLCs) is presented, as well as different methods to reduce the number of model evaluations deriving from the DLCs’ list, and thus reduce computational time.